Effects of structured and unstructured interventions on fundamental motor skills in preschool children: a meta-analysis - Chen, Delong; Zhao, Guanggao; Fu, Jinmei; Shun, Sunli; Su, Liqiang; He, Zihao; Chen, Ruiming; Jiang, Tianle; Hu, Xuewen; Li, Yunong; Shen, Fanchao (Frontiers in Public Health, 2024)
Background: It has been suggested that higher levels of fundamental motor skills (FMS) promote the physical health of preschool-aged children. The impacts of structured and unstructured interventions for FMS among children aged 10-16 years have been widely acknowledged in previous studies. However, there is a lack of relevant studies among preschool-aged children.The aim of this meta-analysis was to compare the effects of structured and unstructured interventions on FMS among preschool-aged children.: The PubMed, Web of Science, and Google Scholar databases were searched from inception to 1 November 2023 to identify experiments describing structured and unstructured interventions for FMS among preschool-aged children. The Downs and Black Checklist was used to assess the risk of bias. A random effects model was used for meta-analysis to evaluate the pooled effects of interventions on FMS. Subgroup analysis based on the duration and characteristics of the intervention were conducted to identify sources of heterogeneity. Results: A total of 23 studies involving 4,068 participants were included. There were 12 studies examining structured intervention, 9 studies examining unstructured intervention, and 6 studies comparing structured versus unstructured interventions. The risk of bias in the included studies was generally low. All interventions significantly improved FMS among preschool-aged children compared to control treatments (P < 0.05). Structured interventions had more significant effects on locomotor skills in preschool-aged children than unstructured interventions (Hedge's g =0.44, P=0.04). The effects of structured interventions were strongly influenced by the total intervention duration, such that long-term interventions were more effective (Hedge's g =1.29, P < 0.001). Conclusion: Structured interventions play a crucial role in enhancing FMS among young children, especially when considering locomotor skills. These interventions require consistent and repeated practice over time to reach proficiency.